Evalutation of the perceived quality in the Orthopedics/Traumatology Unit at Carlo Poma Hospital in Mantova - Pasquali, Daniela; Pizzoli, Andrea; Venturini, Marco; Miglioli, Elena (Acta Biomedica Atenei Parmensis, 2019)
The background and the aim of the work: The Department of Orthopedics and Traumatology of the “Carlo Poma” Hospital (Social Territorial Health Authority of Mantova), has pointed out in 2017, through the questionnaires survey over the citizens satisfaction, an appreciation decrease compared to the previous years. The obtained data were not sufficiently explanatory of the reasons for that kind of deterioration and also not enough specific to define possible corrective measures. The aim of this work was to identify the patients’ perception regarding the hospitalization phases (from booking to follow up), taking into account five kind of operations and pathologies: 1st knee, shoulder and tibio-talar arthroscopy; 2nd hip and knee prosthesis; 3rd upper limb traumatology; 4th lower limb traumatology and 5th orthogeriatrics. Methods: The research is based on 29 narrations resulted from orthopedic patients between 30 and 80 days after the time of discharge. Results: The phases of care path which get the highest level of satisfaction are those concerning the operation and the outpatient visit followed by rehabilitation and assistive continuation. The most negative phase was the discharge but, also the needs assistance respond, the reception, the microclimate and the pre-operative medical assessment resulted contradictory. At the same time the three most significant areas of improvement were: the organization (critical for upper limb traumatology, arthroscopy and prosthetics); the health features (critical for the lower limb, orthogeriatrics and traumatology) and medical information (the most critical issues were those concerning the upper limb traumatology while the less were the orthogeriatrics ones). Conclusion: Use the narration to go into the orthopedic patient needs and perceptions allows to activate appropriate and customized organizational and professional changes in order to answer adequatly to the patient’s needs to limit litigation and defence medicine expences.